PENGARUH MACAM SUMBER BAHAN ORGANIK DAN PUPUK UREA TABLET TERHADAP KARAKTERISTIKKIMIAWI TANAH - -, Rahardjo (MAPETA, 2000)
This study was carried out within 3 months, started from August 22 untul 22 Nopember 1999 on paddy soil at Desa Sidoreja, Kecamatan Pare, Kabupaten Kediri. The soil type used in the study was Regosol. Trial design was factorial randomized block, with 3 replicats. The first factor consisted of organic mailer (8): Azolla (81): Paddy straw (82) and Eceng Gondok (B3) The second factor was dosage of organic matter with 4 level: 0,5,10, and 15 ton ha-1 The result showed that there was no interaction between kind of organic matter dosage and neither for soil pH, CEC, and soil Fe and Mn available. Azolla, Paddy straw, and eceng gondok increasing CEe, soil Fe and Mn on 0 - 20 em. Paddy straw can increase CEC, soil Fe and Mn within 20 - 40 em depth Azalia and paddy straw decreasing soil pH within 0 - 20 em depth but paddy straw decreasing soil pH within 20 - 40 em depth